Night Tourism Routes Selection on BTS Sky Train and MRT Underground in Bangkok and Metropolitan Area Using Multimodal Network - Chaiyakarm , Thanyarat; Sawangdee , Sutasinee (Burapha Science Journal, 2026)
This research aims to analyze the expansion of tourism attractions and entertainment venues from Nighttime Light Imageries in 2012 and 2019 with imagery data from Suomi-NPP VIIRS system. The result showed that in 2012 the area where light reflection value was high only in Bangkok area, which is 0.59 percent of all areas. However, in 2019, light reflection value of formerly low touristy areas began to increase respectively both in Bangkok and Metropolitan area which was 10.71 percent of all areas. From field research in 2019, after collecting 347 stations of locations of attractions and entertainment venues within 400 meters away from Sky Train, underground, roads by using Global Navigation Satellite System (GNSS), as a result, there were 512 of tourism attractions and entertainment venues found. When Average Nearest Neighbor applied in analysis, the result displayed Nearest Neighbor Ratio as 0.369585 which indicated tourism attractions and entertainment venues in night time of Bangkok and Metropolitan area expanded spatially in Cluster form. Thus, it is able to examine and suggest Bangkok’s Night Tourism Routes with Multimodal Network Analysis in 3 routes (1) Metropolitan’s Night market route in 3 networks of transportation modes which are travelling on foot, Sky Train and underground networks within 13.784 kilometers of distance, (2) Don’t Miss Route for foreign tourists with 4 networks of transportation modes which are travelling on foot, Sky Train and underground networks, and public transportation within 42.33 kilometers of distance, and (3) Metropolitan’s Chinese Cultural Educational Route with 3 networks of modes which are travelling on foot, underground and public transportation within 20.642 kilometers. To conclude, appropriate travel plans could be recommended through analysis conditions such as distance and period of time calculated from speed limitation, the numbers of lanes, direction, expense, to meet tourist’s travel objectives.